(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The bacterium Xylella fastidiosa Wells et al., the causal agent of Pierce’s disease of grapevines (PD), was isolated in Balkan Europe. Xylem-feeding Auchenorrhyncha are vectors of the bacterium. In this study the occurrence and phenology of European xylem-feeding Auchenorrhyncha in vineyard habitats, as well as their frequency within grapevine canopies, were investigated in northeastem Italy. The leafhopper Cicadella viridis (L.) and the spittlebugs Aphrophora alni (Fallen), Cercopis vulnerata Rossi, C. sanguinolenta (Scopoli), Lepyronia coleoptrata (L.) and Philaenus spumarius (L.) were found. Cercopis spp. and Ph. spumarius are the cercopid species most likely involved in PD. In fact their adults emerge early in the season and are abundant even within grapevine canopies. Also the leafhopper C. viridis possibly plays a role in the bacterium transmission, particularly in vineyards where the ground is covered by herbaceous vegetation.